Becoming activists in global China - Junker, Andrew (Cambridge : Cambridge University Press, 2019)
Becoming Activists in Global China is the first purely sociological study of the religious movement Falun Gong and its resistance to the Chinese state. The literature on Chinese protest has intensively studied the 1989 democracy movement while largely ignoring opposition by Falun Gong, even though the latter has been more enduring. This comparative study explains why the Falun Gong protest took off in diaspora and the democracy movement did not. Using multiple methods, Becoming Activists in Global China explains how Falun Gong's roots in proselytizing and its ethic of volunteerism provided the launch pad for its political mobilization. Simultaneously, diaspora democracy activists adopted practices that effectively discouraged grassroots participation. The study also shows how the policy goal of eliminating Falun Gong helped shape today's security-focused Chinese state. Explaining Falun Gong's two decades of protest illuminates a suppressed piece of Chinese contemporary history and advances our knowledge of how religious and political movements intersect.
Protest made in global China -- Comparing Falun Gong and Minyun as movements -- The forgotten importance of Falun Gong -- Falun Gong : Qigong fad, new religion, protest movement -- Falun Gong's history of "stepping forward" -- Overseas Minyun : democracy through bureaucracy, factionalism, and asylum.
Title from publisher's bibliographic system (viewed on 13 Feb 2019).
Keywords: Falun Gong (Organization); Social movements -- China; Protest movements -- China; Democratization -- China; Transnationalism -- Political aspects -- China; Chinese -- Political activity -- Foreign countries; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-; China -- History -- Tiananmen Square Incident, 1989.